Implikasi Hukum dalam Penyelesaian Sengketa Perdagangan Internasional Berdasarkan Mekanisme World Trade Organization - Muchamad Edith Afiat Atmaja (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
International trade plays a crucial role in driving the global economy. However, policy differences between countries often trigger disputes that require resolution through fair legal mechanisms. The World Trade Organization (WTO) provides a dispute settlement platform through its Dispute Settlement Body (DSB) to handle these cases. This article explores the legal implications of international trade dispute settlement at the WTO by analyzing the principles of Pacta Sunt Servanda and Distributive Justice. Using a case study of the trade dispute between the United States and China, the article highlights the challenges facing the WTO and the importance of reforming the dispute settlement system to make it more fair and efficient. The conclusion of this study proposes several reform measures needed to improve the effectiveness of the dispute settlement mechanism at the WTO.